Evaluation of Staphylococcus aureus Lipoproteins: Role in Nutritional Acquisition and Pathogenicity - Shahmirzadi, Shideh V.; Nguyen, Minh-Thu; Götz, Friedrich (Frontiers in Microbiology, 2016)
Bacterial lipoproteins (Lpp) represent a major class of membrane proteins. They are distinguished by a lipid moiety at the N-terminus by which they are anchored either in the outer leaflet of the cytoplasmic membrane or, in Gram-negative bacteria, also in the inner leaflet of the outer membrane. In Gram-positive bacteria Lpp significantly contribute to nutrient transport, Toll-like receptor 2 activation and pathogenicity. Here we examine the Lpp of Staphylococcus aureus USA300, as a prototype for a multiple antibiotic resistant and community-acquired pathogen that is rapidly spreading worldwide. The compiled Lpp were grouped according to the postulated function and dissemination of homologs in the genus Staphylococcus and beyond. Based on this evaluation we also point out Lpp as promising vaccine candidates.